Being and sense: the paradox of suffering - Giacoia Junior, Oswaldo (2016)
Taking as an opportunity and philosophical basis of the work of Arthur Schopenhauer, the article presents a reflection on the paradoxical nature of suffering in human existence. Despite its undeniable positivity - only suffering is actually real, well being is always impermanent cessation of suffering - it is absurd, and is implanted in the ontological root of human finitude.